IMPELEMENTASI METODE DRILL DALAM MENINGKATKAN HAFALAN AL-QUR'AN SURAH PENDEK PADA SISWA KELAS IV A DI MADRASAH IBTIDAIYAH IKHLASUL 'AMAL SEBAWI TAHUN PELAJARAN 2021/2022 - Ega Ratnasari; Alkadri; Syaifudin (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
The purpose of this study is to reveal about: 1) teacher preparation before applying the drill method in increasing the memorization of short Al-Qur’an surahs in class IV A students at Madrasah Ibtidaiyah Ikhlasul 'Amal Sebawi for the 2021/2022 academic year; 2) steps taken by the teacher in applying the drill method in increasing the memorization of short Al-Qur’an surahs in class IV A students at Madrasah Ibtidaiyah Ikhlasul 'Amal Sebawi for the 2021/2022 academic year; 3) mastery of memorization after the teacher applies the drill method in increasing the memorization of short Al-Qur’an surahs in class IV A students at Madrasah Ibtidaiyah Ikhlasul 'Amal Sebawi for the 2021/2022 academic year. This study uses a qualitative approach and descriptive research type. Data collection techniques using interviews, observation and documentation. The data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. The research results show that; 1) teacher preparation before applying the drill method in increasing memorization of short Al-Qur’an surahs in class IV A students at Madrasah Ibtidaiyah Ikhlasul 'Amal Sebawi for the 2021/2022 academic year, namely: prepare short surah sheets in advance to distribute to students. After that the teacher invites students to read the surah together slowly and correctly, this activity will be carried out repeatedly. 2) the steps taken by the teacher in applying the drill method in increasing the memorization of the short Al-Qur’an surah in class IV A students are a) The teacher distributes short surahs in sheet form to students; b) The teacher invites students to read it together; c) The teacher asks students to memorize the surah; d) Before depositing the teacher invites students to recite the results of their memorization without looking at the reading text; 3) students' memorization mastery after the teacher applies the drill method in increasing the memorization of short Al-Qur’an surahs in class IV A students is proven when the memorization deposit increases every week.